Calcium sulfate-magnesium oxide composites for antimicrobial and pro-osteogenic bone grafting materials - Liqun Hu; Dongqin Xiao; Shaobin Zhang; Chenxi Ma; Zhuohan Li; Jiyuan Yan; Zhong Li; Kui He; Ke Duan (Materials & Design)
Calcium sulfate (CaS) is a commonly used synthetic bone graft material, but it lacks antimicrobial properties. Magnesium oxide (MgO) has been reported to possess antimicrobial and osteogenic effects in vitro. The present study aimed to develop and evaluate MgO-CaS composites for their antimicrobial and biological properties. MgO nanoparticles were mixed with α-calcium sulfate hemihydrate at 0–25% (w/w). The resultant composites were characterized for setting time, compressive strength, degradation, pH change, and reactive oxygen species (ROS) generation. In vitro inhibition of three pathogens (E. coli, S. aureus, C. alb.), disruption of bacterial biofilm formation, biocompatibility, alkaline phosphatase (ALP) expression, and angiogenic potential were studied. In vivo antibacterial (S. aureus) effects were also evaluated in a rat muscle model. The addition of MgO shortened the setting time and reduced compressive strength. In vitro, the composites exhibited a stable pH plateau and nearly linear degradation profiles; they inhibited bacterial biofilm formation by 18.1–62.0% and reduced the masses of pre-formed biofilms by 38.9–86.5%; they also reduced the formation of bacterial colonies by 87.5–99.0% and fungal colonies by 81.6–97.9%. In vitro biocompatibility decreased with increasing MgO content, but composites with 0–7.5% MgO were non-cytotoxic. ALP levels and angiogenic potential peaked at 2.5% and 7.5% MgO, respectively. In vivo, the composites significantly reduced the retrieved bacterial counts and white blood cell infiltration compared with CaS. These suggest that CaS-MgO composites are effective antimicrobial bone grafting materials with reasonable biocompatibility and potential to reduce infection rates.